The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21037/atm-22-6109
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophage-derived exosomal miR-145-5p protects against the hypoxia/reoxygenation-induced pyroptosis of cardiomyocytes by inhibiting TLR4 expression

Abstract: Background: Exosomes carrying micro ribonucleic acids (miRNAs) protect against myocardial ischemic injury. In the study, we sought to investigate the protective effect mechanism of M2 macrophage-derived exosome miR-145-5p in hypoxia-reoxygenation (H/R)-induced cardiomyocytes.Methods: M2 macrophages were isolated and induced from blood donated by healthy donors. M2 macrophages were transfected with or without miR-145-5p. Exosomes derived from M2 macrophages were isolated and identified by flow cytometry, nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Reduced the activation of caspase-1 PFTU@DEX NPs [ 109] Dexamethasone Acute lung injury LPS-induced ALI mice model Inhibited ROS-NLRP3 pathway NM-LaCD NPs [ 52] 𝛼-cyclodextrin Neutrophilic asthma Neutrophilic asthma mice Attenuate the NETs-mediated inflammasome activation DNA nano-prism [ 97] Buformin/p65 siRNA Acute lung injury LPS-induced ALI mice model Inhibiting the NF𝜅B p65/NLRP3 pathway Disease of cardiovascular system M2 macrophage-derived exosome [ 110] MicroRNA-145-5p Myocardial ischemia/reperfusion injury Hypoxia/reoxygenation AC16 cells model Downregulate the TLR4-NLRP3 pathway PDA-based biomimetic nanoplatform [ 111] Polydopamine Myocardial Ischemia/reperfusion injury MI/RI rat model Suppressing the NLRP3-caspase-1 pathway Calcium carbonate nanoarchitectonics [ 76] Colchicine Acute myocardial infarction MI rat Model Suppressing TLR4/NF𝜅B/NLRP3 pathway…”
Section: Disease Of Respiratory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced the activation of caspase-1 PFTU@DEX NPs [ 109] Dexamethasone Acute lung injury LPS-induced ALI mice model Inhibited ROS-NLRP3 pathway NM-LaCD NPs [ 52] 𝛼-cyclodextrin Neutrophilic asthma Neutrophilic asthma mice Attenuate the NETs-mediated inflammasome activation DNA nano-prism [ 97] Buformin/p65 siRNA Acute lung injury LPS-induced ALI mice model Inhibiting the NF𝜅B p65/NLRP3 pathway Disease of cardiovascular system M2 macrophage-derived exosome [ 110] MicroRNA-145-5p Myocardial ischemia/reperfusion injury Hypoxia/reoxygenation AC16 cells model Downregulate the TLR4-NLRP3 pathway PDA-based biomimetic nanoplatform [ 111] Polydopamine Myocardial Ischemia/reperfusion injury MI/RI rat model Suppressing the NLRP3-caspase-1 pathway Calcium carbonate nanoarchitectonics [ 76] Colchicine Acute myocardial infarction MI rat Model Suppressing TLR4/NF𝜅B/NLRP3 pathway…”
Section: Disease Of Respiratory Systemmentioning
confidence: 99%
“…[120] Using the advantages of exosomes, Li et al harnessed exosomes derived from M2 macrophages to deliver miRNA-145-5p. [110] This approach resulted in the development of a naturally occurring nanomaterial with low immunogenicity and low toxicity, which effectively suppressed myocardial cell apoptosis induced by H/R by downregulating the expression of TLR4. Compared to free drugs, nanoarchitectonics-based drug delivery systems exhibit a prolonged circulation time in the bloodstream, which allows for enhanced accumulation of drugs at the target site, consequently improving therapeutic efficacy.…”
Section: Disease Of Cardiovascular Systemmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of highly conserved, endogenous, single-stranded noncoding small RNAs that regulate gene expression by binding to the 3' untranslated region (UTR) of target mRNA, causing translational arrest or degradation ( 14 ). Emerging evidence has revealed that exosomal miRNAs play a crucial role in insulin resistance and glucose intolerance in both animals and humans ( 15 , 16 ). For example, adipose tissue macrophage (ATM)–derived exosomal miR-155 can cause insulin resistance in vivo and in vitro ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…[21] Concurrent studies corroborate the capacity of M2-Exos to modulate macrophage polarization and temper inflammation. [22,23] Considering the feasibility of biofilm fusion and exosomal liposome fusion, along with the regulatory influence wielded by M2-Exos and BMSCs-Exos on macrophage polarization, a novel milestone has been achieved through the creation of M2-Exos and BMSCs-Exos fused exosomes (M2-BMSCs-Exos). This groundbreaking achievement seamlessly amalgamates immune resistance with precise targeting of osteolysis sites, effectively harnessing the therapeutic potential of two distinct exosome types.…”
Section: Introductionmentioning
confidence: 99%